TEXT-BASED SYLLABUS DESIGN AND ITS IMPLEMENTATION IN ACADEMIC WRITING CLASSROOM : A Case Study Conducted to One Lecturer in One Public University in Bandung, Indonesia - Maesaroh, Raden (2014)
The study is concerned with the investigation of a text-based syllabus design and its implementation in academic writing classroom involving one non English department lecturer as the participant. This was conducted based on a consideration that writing a research paper abstract in English for non English lecturer is difficult. The aims of the study were to find out the effectiveness of a text-based syllabus design in teaching writing a research paper abstract in academic writing classroom, to seek the gaps between the syllabus and its use in the classroom and to expose the strategies used to anticipate the gaps. The study employed a qualitative research design and used a case study method. It was carried out within ten meetings including six meetings of teaching, one meeting of review and three meetings of test. In the study, the researcher acted as the syllabus designer, learning material developer and teacher. As aforementioned, the study involved one non English lecturer of one public university in Bandung, Indonesia. The data were collected by using three types of instruments including classroom observation, interview and document analysis. The observation was conducted by recording the teaching program, documenting what was done and said by the teacher and the participant. A colleague was invited as another observer to verify the data and validate the study. Apart from that, the interview was semi-structured one which was carried out in an ongoing way and at the end of the program. In an ongoing basis, the interview was conducted after each lesson was implemented, asking the impression of each lesson including its strong and weak points. At the end of the program, the interview was carried out after the teaching program was conducted, asking the participant's perception, the benefits and the strong and the weak points of the whole program. The end interview also asked the suggestions for the improvement of the program. In terms of document analysis, several documents were observed including, the syllabus, lesson plan, learner's written work (tasks in independent construction and tests) and learning materials. The results showed that; (1) despite some limitations, the text-based syllabus design was effective in most parts in the teaching of writing research paper abstract. The participant better performed in her writing in that she showed a clear text structure, appropriate skeletal phrases and better language features in the research paper abstract writing. It was accompanied with her awareness of having the progress in terms of research paper abstract writing and her good understanding that writing is a recursive process as viewed from the data of interview and documents analysis; (2) the data from the document analysis and observation showed that the gaps occurred between the lesson plan and the teaching and it was attended in four following aspects, namely steps of teaching, activities, learning materials and time; (3) in order to anticipate the gaps, the teacher used different strategies to the teaching, to the lesson plan and the materials. In terms of the teaching, the teacher applied context adjustment (steps of teaching, activities and time), whereas in terms of lesson plan, the teacher employed reorganization and simplification. Further, in the case of materials, the teacher utilized modification and simplification.